Pengaruh Disiplin Kerja, Komunikasi Kerja, dan Kerjasama Terhadap Kinerja Pegawai di Dinas Kesehatan Kota Batam - Alviani, Maylan; Dewi, Nolla Puspita; Wahyuni, Etty Sri (Universitas Batam, 2024)
As social beings, humans have individual characteristics that differ from each other and always strive and depend on others to meet their life needs. This study aims to find out how work discipline affects staff performance; how work communication affects employee performance; How Collaboration affects employee performance; and how discipline, communication, and collaboration affect staff performance at the Batam City Health Service. This study uses a quantitative approach. The type of survey research used is a questionnaire used to gather information from participants. The study took samples from all of the Health Service employees, a total of 126 people, using saturated sampling techniques. This research uses both types of data analysis: descriptive and quantitative analysis. The results of the study show that work discipline has a positive and significant impact on employee performance in this study, as demonstrated by the 7.373 t value above 1.979 and a significant value of 0,000 below 0.05. Furthermore, the test results show that the work communications variable has a positively and significant effect on the performance of employees in the Batam City Health Service, this is proved by obtaining the 3.798 t score greater than 1.979, and the significant 0.000 value below 0.05 Then the test result showed that, although not significant, the impact of cooperation on the employee's performance in Batam Municipal Health Service has positive but non-significant impact. This is shown by the t value of 0.553 below 1.978 and a significant value of 0,595 above 0.05 Further, it is seen that independent variables such as work disciplines, work communication, and cooperation work have a similarly positive impact on staff performance. The F test result showed 126,830 greater than the F table of 2.68 with a significant value of 0,000 less than 0.05